Redox-tagged peptide for capacitive diagnostic assays - Santos, Adriano [UNESP]; Piccoli, Julia P. [UNESP]; Filho, Norival A.s.; Cilli, Eduardo Maffud [UNESP] (Elsevier, 2014)
Early detection assays play a key role in the successful treatment of most diseases. Redox capacitive biosensors were recently introduced as a potential electroanalytical assay platform for point-of-care applications but alternative surfaces (besides a mixed layer containing ferrocene and antibody receptive component) for recruiting important clinical biomarkers are still needed. Aiming to develop alternative receptive surfaces for this novel electrochemical biosensing platform, we synthesized a ferrocene redoxtagged peptide capable of self-assembly into metallic interfaces, a potentially useful biological surface functionalization for bedside diagnostic assays. As a proof of concept we used C-reactive protein (CRP), as a model biomarker, and compared the obtained results to those of previously reported capacitive assays. The redox-tagged peptide approach shows a limit of detection of 0.8 nmol L 1 (same as 94 ng mL 1 ) and a linear range (R2 ∼98%) with the logarithm of the concentration of the analyte comprising 0.5–10.0 nmol L 1 , within a clinical relevant range for CRP.
Keywords: Electrochemical capacitance spectroscopy; Ferrocene-tagged peptide; Label-free redox capacitance biosensing; Binding affinity constant